Estudo da produtividade no processo de cristalização de ácido cítrico em leito vibrado - Teixeira, Gustavo Araújo (2011)
The aim of this work was study the phenomenological concepts, operational and, above all, mass productivity in the crystallization of citric acid in vibrated bed, using large population of seeds (dense phase). It was used a truncated conical stainless steel crystallizer, containing a mobile central axis with coupled perforated disks, transferring vibrational energy to the crystallization environment. It was conducted a representation of the crystallization suspension environment flow of crystalline particles that illustrated the process of bed fluidization. The solution initially saturated, to its saturate temperature, was taken to the crystallization temperature 55°C, becoming supersaturated, and seeded with commercial grainy citric acid crystals. It was used as statistic toll a central composite design to construct a representative model and influence verification of process significant variables: crystallization time, a degree of supersaturation and intensity of vibration. The response analyzed was the productivity (mass percentage increase) in crystallization process. Using the model obtained, it was calculated the maximum productivity condition in mass, which consisted a percentage increase in mass of 164.7%. This condition was posteriorly tested in the experimental unit resulting in an productivity of 187.7%. The crystallizers in series simulation occurred using commercial citric acid seeds with the same final diameter of the tests using the optimized conditions, keeping other variables constant, resulting in a mass percentage increase, for the second step, of 166.9%. These showed efficiency in obtaining crystals with larger end. Was performed to evaluate the secondary nucleation by capturing the image of crystals in crystallization trials, where was noticed the appearance of small polycrystalline structures in the crystalline surface of the crystals, caused by the high degree of supersaturation, or due to the systematic separation of these